Effect of soil moisture stress on growth and yield of cassava in Nigeria - Aina, O.O.; Dixon, Alfred G.O.; Akinrinde, E.A. (2007)
Nine cassava genotypes were evaluated for their growth responses and adaptability to soil moisture stress on the field and in the screen house in Nigeria. Genotypes were evaluated in three savanna agroecologies in a randomized complete block design with three replicates. Screen house evaluation was conducted using three moisture regimes of 75, 50 and 25% Field Capacity (FC) in a two-factor factorial experiment in CRD with three replicates. Morphological and yield data were collected on the field and in the screen house. Results showed significant (p < 0.05) difference among genotypes on the field and in the screen house. Field moisture stress led to a decline in plant height by 47%, stem girth by 15%, number of tubers by 95% and tuber yield by 87%. Screen house moisture condition of 25% FC led to a reduction in plant height by 12.6 and 21.2%, stem girth by 16.3 and 21.7%, number of roots by 94.5 and 88.7% and root weight by 93.3 and 94.9%, respectively at 16 and 30 WAP. Moisture stress therefore resulted into considerable reduction in both vegetative growth and yield of cassava genotypes. Therefore, a concerted effort in breeding cassava for drought tolerance is needed as cassava cultivation is expanding into nontraditional semiarid regions of sub-Saharan Africa. Germplasm introduced from Latin America (especially north-eastern Brazil) is providing a unique source of variability to further broaden the genetic base for drought tolerance in cassava.